2016
DOI: 10.1177/0960327115626583
|View full text |Cite
|
Sign up to set email alerts
|

Mitigation of 5-fluorouracil–induced liver damage in rats by vitamin C via targeting redox–sensitive transcription factors

Abstract: Adverse complications associated with antineoplastic drug-based cancer therapy are the major clinical drawbacks. Oxidative stress and inflammation play a major role in the damage due to cancer therapy. In the current study, we investigated the modulatory effect of vitamin C (Vit. C) on liver toxicity induced by 5-fluorouracil (5-FU) in rats. Animals were divided into four groups. Animals in group I received vehicle. Oral gavage of Vit. C (500 mg kg−1 body weight (b.wt.)) was given… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 50 publications
3
23
0
Order By: Relevance
“…However, previous research has shown that 5-FU causes nephrotoxicity [19] and hepatotoxicity [29]. These contradictory results may be due to the higher concentration of 5-FU used in these studies.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…However, previous research has shown that 5-FU causes nephrotoxicity [19] and hepatotoxicity [29]. These contradictory results may be due to the higher concentration of 5-FU used in these studies.…”
Section: Discussionmentioning
confidence: 78%
“…In our study, the physiological function of liver, kidney and lung tissue examined by H&E staining showed no obvious differences among BA (5 and 10 mg/kg), 5-FU (10 mg/kg) and the non-treated control. However, previous research has shown that 5-FU causes nephrotoxicity [ 19 ] and hepatotoxicity [ 29 ]. These contradictory results may be due to the higher concentration of 5-FU used in these studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of 5-FU were metabolized in the liver, and only about 15% of 5-FU were eliminated from the human body as the original urine. Moreover, Long term application of 5-FU can lead to liver injury [ 26 ]. Alanine transaminase (ALT) and aspartate transaminase (AST) are mainly distributed in liver cells, and their increased levels are consistent with the degree of liver cell damage.…”
Section: Discussionmentioning
confidence: 99%
“…This experimental design was as described by Al-Asmari et al 6 Wistar rats were randomly divided into six different groups (n=6 each). The first group received normal saline (1 mL/kg) and used as a negative control.…”
Section: Experimental Designmentioning
confidence: 99%